Bibliometric Insights into Computational Thinking and Green Computing Awareness: Emerging Trends Toward Sustainable Digital Pedagogy (2015–2024) - Ria, Reny Refitaningsih Peby; Yuda, Lalu Setia; Patty, Elyakim Nova Supriyedi (Universitas Muhammadiyah Palu, 2025)
The digital transformation in higher education requires the integration of computational literacy and environmental awareness to achieve sustainable learning practices. This study aims to map the interrelation between Computational Thinking (CT), Green Computing Awareness (GCA), and the use of statistical analysis software within the framework of Sustainable Digital Pedagogy. The research employed a descriptive bibliometric approach. The dataset consisted of 60 documents refined from the Scopus database covering the 2015–2024 period. Data were analyzed using the analyze results feature on the Scopus website and the VOSviewer software to identify publication trends, thematic networks, and the global evolution of related studies. The findings reveal that CT occupies the most central position in the research landscape, while GCA forms an independent cluster emphasizing energy efficiency and technological sustainability. The use of statistical analysis software serves as a conceptual bridge between the two domains. These findings highlight the need for an integrative approach that combines cognitive, ecological, and analytical dimensions in higher education. This study provides conceptual insights and strategic implications for developing curricula and green digital campus policies oriented toward sustainability.